CHAPTER II. PROBLEMS AND SOLUTIONS OF TOURISM TERMS IN INTERPRETATION - Yunusova Shaxlo Bashirillayevna (PEDAGOGS, 2024)
Theoretical lexicography deals with the history of lexicography, types of dictionaries, requirements for dictionaries, critical analysis of existing dictionaries, practical lexicography deals with the study, compilation, improvement and consumption of a certain type of vocabulary. Practical lexicography involves the application of general theoretical principles and rules of lexicography in the process of creating a dictionary.The vagueness of terms, their meanings, the essence of the notion, excessive length, complex sentences, and an excessive number of foreign terms are inconvenient. In response to the aforementioned issues, modern lexicography must create a glossary of terms in many professions. From the beginning to the finish of the terminology system development process, a lexicographer must collaborate with a specialist in the topic. This is for a variety of reasons. The lexicographer can quickly provide accurate and extensive explanations of words, as well as generate examples of authorship, when creating a dictionary of common words. As a result, monolingual dictionaries cover a greater number of terms than translation dictionaries. The functional value of the term is vital in practical translation dictionaries; that is, the user must be able to use the dictionary to grasp a specific word in the correct context, from a communication standpoint, and for himself/herself.